Investigating the first user experience and accessibility of educational applications for autistic children - Branco, Karina da Silva Castelo; Pinheiro, Valéria Maria da Silva; Damian, Adriana Lopes; Marques, Anna Beatriz (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
The use of technologies for teaching children with Autistic Spectrum Disorder (ASD) has been addressed by many authors, but it is still relevant to investigate whether the applications developed for this target audience promote positive user experience. This paper reports a study that evaluates educational applications developed for children with ASD, focusing on their first experience of use and accessibility aspects related to ASD. The study was conducted in Jaguaruana city and the participants were ten autistic children and their mothers. The first experience of use was monitored and evaluated by observation and questionnaires. Additionally, an accessibility inspection was conducted by three evaluators to identify interface accessibility problems. The results indicate positive aspects concerning the ease of learning to use the applications. On the other hand, our research revealed negative results related to the children's mood changes. We noticed that a child with a higher level of ASD faced more difficulties to maintain attention during the use of applications. In addition, these children demonstrate irritation when failing to perform the challenges. Some improvements can be made in the evaluated applications for a better user experience. Thus, this research contributes to the use of Human-Computer Interaction (HCI) evaluation methods with users and specialists to evaluate educational applications for autistic users.